Unraveling the G protein-coupled receptor superfamily in aphids: Contractions and duplications linked to phloem feeding - Gao, Han; Li, Yanxiao; Zhang, Xianzhen; Zhang, Hui; Tian, Ying; Li, Bin (General and comparative endocrinology, 2024)
•The number of GPCR genes in R. maidis, A pisum and A gossypi were 97, 105 and 95.•A contracted GPCR superfamily was discovered in aphids.•GPCRs putatively associated with feeding a liquid diet were duplicated. The G Protein-Coupled Receptor (GPCR) superfamily is the largest and most diverse transmembrane receptor family, playing crucial roles in regulating various physiological processes. As one of the most destructive pests, aphids have been subject to previous studies, which revealed fewer GPCR superfamily members in Acyrthosiphon pisum and Aphis gossypii and the loss of multiple neuropeptide GPCRs. To elucidate the contraction patterns and evolutionary features of the aphid GPCR superfamily, we identified 97, 105, and 95 GPCR genes in Rhopalosiphum maidis, A. pisum, and A. gossypii, respectively. Comparative analysis and phylogenetic investigations with other hemipteran insects revealed a contracted GPCR superfamily in aphids. This contraction mainly occurred in biogenic amine receptors, GABA-B-R, and fz families, and several neuropeptide receptors such as ACPR, CrzR, and PTHR were completely lost. This phenomenon may be related to the parasitic nature of aphids. Additionally, several GPCRs associated with aphid feeding and water balance underwent duplication, including Lkr, NPFR, CCHa1-R, and DH-R, Type A LGRs, but the SK/CCKLR that inhibits feeding was completely lost, indicating changes in feeding genes that underpin the aphid's prolonged phloem feeding behavior. Furthermore, we observed fine-tuning in opsins, with reduced long-wavelength opsins and additional duplications of short-wavelength opsin, likely associated with daytime activity. Lastly, we found variations in the number of mthl genes in aphids. In conclusion, our investigation sheds light on the GPCR superfamily in aphids, revealing its association with diet lifestyle and laying the foundation for understanding and developing control strategies for the aphid GPCR superfamily.